FACTORS AFFECTING SOCIALLY RESPONSIBLE INVESTMENT INTENTIONS INVESTORS IN SURABAYA - Jesselyn Geraldine; R. Shanti D. Ottemoesoe (Finance and Investment Program, School of Business and Management - Petra Christian University, 2021)
Socially responsible investment (SRI) is an investment that considers financial goals and non-financial goals such as social, ethical, and environmental-related matters. This study aims to examine the factors that influence SRI intentions on 113 investors in Surabaya using the theory of reasoned action (TRA), attitude and subjective norms, and three additional variables, namely moral norms, financial literacy, and returns. The research data was obtained from distributing questionnaires through Google Forms. Data processing is carried out using Partial Least Square's method with the SmartPLS application. The study results found that all study's independent variables had a significant positive effect on SRI intentions.